Peptide mimetic of N‐terminal ghrelin enhances ghrelin‐induced growth hormone secretion and c‐Fos expression in mice. (22nd November 2018) - Lunder, Mojca; Vodnik, Miha; Kubale, Valentina; Grgurevič, Neža; Majdič, Gregor; Štrukelj, Borut
Abstract : Orexigenic peptide ghrelin and its receptor have been extensively investigated as potential therapeutic targets, primarily because of their role in feeding initiation and growth hormone (GH) release. However, no specific ghrelin targeting anti‐obesity or cachexia therapeutics are available for clinical use thus far and further efforts in this direction are warranted. The present study aimed to find new peptide drug leads modulating ghrelin signal transduction. By targeting neutralising antibodies against ghrelin with phage display libraries, we aimed to identify peptides binding to the cognate receptor. Four synthetic peptides were selected and tested using calcium screening assays. The most effective competitive antagonist FSFLPPE was further tested in vivo. Administration of the peptide produced no significant effect on either food intake or GH release. Surprisingly, when co‐administered with ghrelin, the peptide significantly enhanced GH secretion and c‐Fos expression. The evidence obtained in the present study indicates that FSFLPPE might act as an ago‐allosteric modulator.